Hukum Islam dan Perubahan Sosial: Studi atas Konsep Mas}lah}ah dan Aplikasinya dalam Hukum Keluarga Islam Kontemporer - Yoyo Hambali (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2015)
The focus of this paper is the problem of how the concept maslahah and its application in contemporary of law of Islamic family. The approach of this paper is the sociological approach and social history of Islamic law. The conclusion of this paper, among others that since the early days of Islam and the rise of the mujtahid scholars, as well as the next generation, ijtihad is done to decide new issues that arise as social change by making maslahah as the basis and legal considerations. In the contemporary times, cases of family law that emerged during this period, such as interfaith marriage, marry a pregnant woman, marriage contract, adoption of children with the listing, the status of a child born out of wedlock, and other cases, it can be decided legal with the basic of maslahah, namely to realize the benefit and prevent damage. Thus, consideration of maslahah can be the basis in istinbat of Islamic law that should not be overlooked simply because the law is decided in order to create the benefit of human life.